Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1073/pnas.0508239102
|View full text |Cite
|
Sign up to set email alerts
|

Development of spectral and temporal response selectivity in the auditory cortex

Abstract: The mechanisms by which hearing selectivity is elaborated and refined in early development are very incompletely determined. In this study, we documented contributions of progressively maturing inhibitory influences on the refinement of spectral and temporal response properties in the primary auditory cortex. Inhibitory receptive fields (IRFs) of infant rat auditory cortical neurons were spectrally far broader and had extended over far longer duration than did those of adults. The selective refinement of IRFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
160
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(176 citation statements)
references
References 37 publications
13
160
2
Order By: Relevance
“…These data are reminiscent of recent findings showing that the timing of the AI critical period can be altered by exposure to different auditory environments 10,12 .…”
supporting
confidence: 61%
“…These data are reminiscent of recent findings showing that the timing of the AI critical period can be altered by exposure to different auditory environments 10,12 .…”
supporting
confidence: 61%
“…By contrast, previous studies that applied continuous noise exposure during the critical period reported that noise-rearing did not necessarily permanently impair cortical temporal processing into adulthood; the cortex returned to ''normal'' after animals were returned to a normal acoustic environment (13,14). A similar difference in the duration of exposure-induced plasticity has been reported in spectral domain development of A1 when rats were exposed to pulsed (11,12) or continuous (13) noise during the critical-period epoch.…”
Section: Discussionmentioning
confidence: 63%
“…Using a two-tone stimulus paradigm, it has been shown that the duration of poststimulation suppression significantly influences the ability of cortical neurons to respond to successive acoustic stimuli (14). Here, we estimate the dynamics of cortical excitability, using compound PSTHs generated by tonal stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, changes in PV connectivity during postnatal development may allow for the maturation of simple receptive field organization. For instance, appropriate developmental inhibitory receptor activation is necessary for the normal reduction in spatial extent and temporal duration of receptive fields in primary sensory cortex (Chang et al, 2005).…”
Section: Involvement Of Pv Interneuron Connectivity In the Developmenmentioning
confidence: 99%